Construção de sujeitos políticos: trajetórias de conselheiros municipais de saúde - Aparecida Rosangela Silveira (2014)
This thesis analyzes the trajectories of construction of political subjects in health policy. The general aim was to elucidate the processes involved in the trajectories taken by municipal health counselors from the community where they belong up to their inclusion in participatory forums. The empirical research adopted a qualitative approach using the Grounded Theory as a methodology for collecting and analyzing data on a social constructionist and interpretive strand. Based on the profile of the municipal health counselors, two sample groups were defined and intensive interviews and field observations were conducted. The seventh version of the Atlas.ti software was used as support for analysis of the collected data. Data analysis adopted sensitizing concepts about logical recognition, linguistic processes and interaction processes. Four moments belonging to the trajectories of the subjects traversed by contingencies were identified: the establishment of primary relationships of recognition and construction of identification processes within the family context; the expansion of relations of recognition and manifestation of singularities in the enlarged group; the establishment of references for insertion into social movements and political engagement; and the strengthening and expansion of participation in contexts of conflict and differences. By means of the identified moments, the central theory of this thesis was established: the political subject is a process in permanent construction with different contours, gathering singularities, relations of recognition and networks of meanings.